Performance Analysis of Wireless Sensor Network Using Cognitive Radio Concept - Pawar, Rujuta V; Mahajan, Swati S (International Journal of Computer Sciences and Engineering, 2014)
As the demand for wireless increases there is rapid development of various wireless technologies. The users want to use wireless communication services anytime and anywhere. Wireless Sensor Networks (WSNs) are expected to play an important role in future to provide reliable data transmission. But the traditional WSN works in unlicensed band and suffer from uncontrolled interferences from the networks sharing the same spectrum. As it resides in high Bit Error Rate there is increased delay in data transfer which results in less throughput. In this paper the WSN using cognitive concept is studied for reliable data transmission.